Myocardial Lipin 1 knockout in mice approximates cardiac effects of human LPIN1 mutations - Kari T. Chambers; Michael A. Cooper; Alison R. Swearingen; Rita T. Brookheart; George G. Schweitzer; Carla J. Weinheimer; Attila Kovacs; Timothy R. Koves; Deborah M. Muoio; Kyle S. McCommis; Brian N. Finck (JCI Insight, 2021)
Lipin 1 is a bifunctional protein that is a transcriptional regulator and has phosphatidic acid (PA) phosphohydrolase activity, which dephosphorylates PA to generate diacylglycerol. Human lipin 1 mutations lead to episodic rhabdomyolysis, and some affected patients exhibit cardiac abnormalities, including exercise-induced cardiac dysfunction and cardiac triglyceride accumulation. Furthermore, lipin 1 expression is deactivated in failing heart, but the effects of lipin 1 deactivation in myocardium are incompletely understood. We generated mice with cardiac-specific lipin 1 KO (cs-Lpin1–/–) to examine the intrinsic effects of lipin 1 in the myocardium. Cs-Lpin1–/– mice had normal systolic cardiac function but mild cardiac hypertrophy. Compared with littermate control mice, PA content was higher in cs-Lpin1–/– hearts, which also had an unexpected increase in diacylglycerol and triglyceride content. Cs-Lpin1–/– mice exhibited diminished cardiac cardiolipin content and impaired mitochondrial respiration rates when provided with pyruvate or succinate as metabolic substrates. After transverse aortic constriction–induced pressure overload, loss of lipin 1 did not exacerbate cardiac hypertrophy or dysfunction. However, loss of lipin 1 dampened the cardiac ionotropic response to dobutamine and exercise endurance in association with reduced protein kinase A signaling. These data suggest that loss of lipin 1 impairs cardiac functional reserve, likely due to effects on glycerolipid homeostasis, mitochondrial function, and protein kinase A signaling.